Innovative Digital Approaches to Physics Teaching through STEAM Integration - Faridatul Laili; Khoirun Nisa’ (Journal of Digitalization in Physics Education, 2025)
Objective: This study aims to analyze the development of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach in physics learning in Indonesia. It explores various aspects commonly investigated in related studies, such as types of research, subjects, instruments, physics topics, measured variables, learning media, findings, and research recommendations. Method: This research employs a literature review method, using secondary data collected from relevant scientific journals published in Indonesia. The analysis focuses on identifying patterns and trends in the implementation of STEAM-based physics education. Results: The results indicate that the STEAM approach has a significant positive impact on physics learning. It enhances students’ creativity, conceptual understanding, critical thinking, and overall learning outcomes. Various learning media, especially digital tools, have been integrated effectively within the STEAM framework. However, some challenges remain, such as aligning STEAM implementation with the national curriculum and managing limited classroom time. Novelty: This study provides a comprehensive overview of how STEAM has been applied in physics education in the Indonesian context. It highlights key trends, benefits, and barriers, offering valuable insights for educators and policymakers aiming to integrate interdisciplinary, digitally enriched learning approaches into physics instruction.